PENGARUH KUALITAS PELAYANAN RBC DAN FOC TERHADAP KEPUASAN KONSUMEN HOTEL DI KABUPATEN BADUNG - Ida Ayu Agung Ngurah Indrawati (Jurnal Ilmiah Hospitality Management, 2017)
The purpose of this research was to examine the effect of restaurant and bar cashier and front office cashier service on customer satisfaction. The research method used was Non Probability Sampling technique by using Accidental Sampling as the sampling method. The research was conducted in four and five star hotels in Badung regency, period of 1 September until 1 October 2015. Data collection techniques used were interview, observation, and literature study. Meanwhile, descriptive and multiple linear regression were used as data analysis technique. The result showed that the restaurant and bar cashier and front office cashier service quality had a positive and significant effect on customer satisfaction.With the regression equation is: Customer Satisfaction = 9,947 - 0,193 KKD + 0,314 KRB + e, or can be interpreted that if the independent variable was considered fixed, then the consumer satisfaction would increase 9.947. If the front office cashier service was increased by one unit, then the consumer satisfaction would l increase by 0.187 units. If the restaurant and bar cashier service was increased by one unit, then the consumer satisfaction would increase by 0.314 units.